ANTIOXIDANT ACTIVITY, PHYSICAL QUALITY, AND SENSORY PROPERTIES OF WATERMELON ALBEDO (Citrullus lanatus) ICE CREAM WITH HONEY - Mahmudah, Nur Aini; Hariyanti, Asih Putri; Luthfiya, Lulu’; Sari, Fitri Komala (Jurnal Sains dan Teknologi Pangan, 2023)
Antioxidant are nutritional and non-nutritional substances within in food preventing or slowering oxidative damage in the body. Antioxidant can be obtained by consuming healthy foods, fruits, and vegetables. Watermelon’s albedo and honey are both containing antioxidant which have the opportunity to be developed into products such as ice cream. This study aimed to determine the antioxidant activity, physical quality, and sensory properties of watermelon albedo ice cream with the addition of honey. This research was conducted experimentally by a completely randomized design (CRD), with four treatment levels. The ratio of watermelon albedo and honey were 30%:0%, 30%:10%, 20%:20%, and 10%:30%. Analysis carried out were antioxidant activity, physical quality (overrun, melting speed, and total solids), and sensory properties (color, aroma, taste, and texture). There was no significant difference in antioxidant activity of all ice cream samples (F0, F1, F2 and F3). The physical quality analysis resulted there were significant differences in melting speed and total solids parameters. The organoleptic quality test resulted that panelist preferred ice cream without the addition of watermelon albedo and honey.